2019
DOI: 10.1111/nhs.12649
|View full text |Cite
|
Sign up to set email alerts
|

Nursing assistants' perceptions of their role in the resident experience

Abstract: The aim of this study was to examine nursing assistants' perspectives of their role in the nursing home resident experience. Recent efforts to improve nursing home quality are focused on providing person‐centered care and improving the resident experience. However, the literature on nursing home quality lacks the perspective and experiences of nursing assistants themselves, despite their crucial role in the resident experience. Semistructured interviews were conducted with 25 nursing assistants from 17 organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Registered nurses are a minority in the workforce of nursing homes, with the majority of positions being held by nursing assistants [ 22 ]. However, most nursing assistants in Chinese nursing homes are not well educated, their social and economic status is usually lower than middle class, and most of them do not have knowledge of professional care concepts [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Registered nurses are a minority in the workforce of nursing homes, with the majority of positions being held by nursing assistants [ 22 ]. However, most nursing assistants in Chinese nursing homes are not well educated, their social and economic status is usually lower than middle class, and most of them do not have knowledge of professional care concepts [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A literature review found that one reason for people becoming nursing assistants was a wish to contribute to patient care (Hewko et al., 2015), suggesting that some nursing assistants already had a strong sense of their desired roles when they started to work. Additionally, previous studies showed that nursing assistants were aware of minor changes in patients, as they were close to the patients, and perceived their role in patient care and safety as communicating with patients (Abrahamson et al., 2019). Therefore, nursing assistants may have higher perceptions of their desired roles than nurses expect, since they perceive close relationships with patients and engage in daily patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous studies showed that nursing assistants were aware of minor changes in patients, as they were close to the patients, and perceived their role in patient care and safety as communicating with patients (Abrahamson et al, 2019). Therefore, nursing assistants may have higher perceptions of their desired roles than nurses expect, since they perceive close relationships with patients and engage in daily patient care.…”
Section: Nursing Assistants' Perceptions Of Their Desired Roles and Nurses' Expectations Of Nursing Assistantsmentioning
confidence: 98%
See 2 more Smart Citations